Gender Differences in Stress Resistance of Adolescents with Autism Spectrum Disorders - Yakymchuk, Iryna; Vakhotska, Iryna; Radzivil, Kateryna; Ivashchenko, Kateryna; Poliekhina, Viktoriia (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Objective: The research provided the empirical study of the gender differences in the experience of stress and coping with it in boys and girls diagnosed with high-functioning autism through qualitative methods. Methods: Observation was the main method used in the study, which was implemented by filling in the observation diary by specialists and parents of adolescents with autistic disorders. The main coping strategies under research were addressing others, avoiding the problem, and working on the problem. Content analysis was used as the main data processing method. Results: The study found some gender differences in coping with stress between males and females. Besides, it was found that the use of certain forms of coping behavior differs depending on age. Conclusions: The study allowed us to determine that boys tend to choose a strategy of working on the problem in interpersonal interaction, while girls are disposed to avoid the problem. The opposite picture was observed for the social environment: girls with ASD tend to use a strategy of addressing others, and boys avoid the problem through self-isolation.